Analysis of the Status of Non "State Civil Apparatus" Employees on the Performance of the DPRD Secretariat of Kaltim Province - Widya Putri Nurchasanah; M Saleh Mire; Zainal Abidin (International Journal of Economics and Management Research, 2024)
An organization or company will operate well when it has superior and competent human resources. Human resources greatly influence the operation of an institution. Human resources are the thinkers, drivers, and planners to achieve the best goals in the organization or company. To reach the point of success, an organization or company must pay attention to its human resources by improving employee performance. The Regional House of Representatives of East Kalimantan Province (DPRD PROV KALTIM) has employees consisting of both ASN (State Civil Apparatus) and Non-ASN, which obviously have differences. Therefore, the purpose of this study is to analyze how employee status affects performance and to analyze the performance of Non-ASN employees at the Secretariat of the Regional House of Representatives of East Kalimantan Province. The research method used in this study is a qualitative approach. The results of the research indicate that the status of Non-ASN employees influences their performance. This influence is positive because Non-ASN employees strive to complete all tasks assigned by their superiors as well and as optimally as possible, and they complete these tasks on time. Despite their status as Non-ASN, they still perform their duties and obligations similarly to ASN employees. The performance of Non-ASN employees shows their sense of responsibility towards the workload given, and each workload is adjusted to the employees' capabilities, making them comfortable in their work and understanding what needs to be done.